Pengembangan Model Integrated Writing and Practice Cycle (IWPC) untuk Meningkatkan Keterampilan Writing dan Speaking Siswa SMP - Ebit N Rauf (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
English language instruction at the junior high school level often faces challenges due to the separation of writing and speaking skills, which limits students’ productive communicative competence. This study aims to develop and examine the effectiveness of the Integrated Writing and Practice Cycle (IWPC) model in improving junior high school students’ writing and speaking skills. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were eighth-grade students from SMP Muhammadiyah 6 and MTs Muhammadiyah 2 Al-Munawwaroh Malang. Data were collected through classroom observations, questionnaires, interviews, and writing and speaking tests. Both quantitative and qualitative analyses were applied to examine the validity, practicality, and effectiveness of the model. The findings reveal that the IWPC model is highly valid based on expert judgment, practical according to teacher and student responses, and effective in enhancing students’ writing and speaking skills. Learning improvement was indicated by Normalized Gain (N-Gain) scores ranging from moderate to high levels. Qualitative results also demonstrate positive changes in students’ learning behavior, particularly increased writing autonomy, speaking confidence, and active classroom participation. In conclusion, the IWPC model serves as an effective integrative and reflective instructional model for English language learning at the junior high school level and aligns well with the principles of the Merdeka Curriculum